Accelerated denaturation bubble-mediated strand exchange amplification for rapid and accurate detection of canine parvovirus. Issue 45 (9th November 2020) - Hou, Jie; Li, Yang; Ma, Cuiping; Shi, Chao
Abstract : A novel nucleic acid amplification technology, accelerated denaturation bubble-mediated strand exchange amplification (ASEA), could detect canine parvovirus (CPV) genomic DNA at a concentration of 8.0 × 10 –18 M within 16.6 min. Abstract : Canine parvovirus (CPV), a strong infectious canine pathogen, has been recognized as a threat to canine health worldwide since the 1970s. Although convenient detection methods have been developed, such as the colloidal gold test strip, most of these methods are based on antibody detection, which is relatively ineffective for detecting pathogens during the incubation period. For institutions and businesses with many dogs, e.g., dog training centers and kennels, more sensitive detection methods are required to prevent the swift spread of CPV. Thus, we developed accelerated denaturation bubble-mediated strand exchange amplification (ASEA) for CPV detection, and it is a rapid, convenient, and cost-effective method. ASEA was able to distinguish CPV genomic DNA in a mixture that included canine genomic DNA as well as nucleic acids sourced from nine other common pathogens, with detection of target DNA as low as 8.0 × 10 −18 M within 16.6 min. Coupled with the thermal lysis method modified by us that only requires 3 min to perform, the entire detection procedure can be completed within approximately 20 min and only requires a simple heating block and an ordinary fluorescence PCR instrument. Moreover, ASEA exhibited greater sensitivity than colloidal gold test strips in actual specimen detection. This technique is rapid, easy to perform, and highly sensitive, and therefore, this approach has the potential to rapidly detect CPV in institutions with large populations of dogs.